Pengaruh Luas Lahan terhadap Pendapatan Usahatani Kedelai di Kecamatan Toari Kabupaten Kolaka - Purbaningsih, Yuli (Department of Agribusiness, Halu Oleo University, 2020)
This research aims to find out the level of technical efficiency of the use of production factors in soybean farming (Glycine max L Merrill) in Toari Sub District of Kolaka District. The research method used is quantitative research with a survey approach. The determination of samples is done by the census. The object of the study was 30 farmers as respondents. Data is collected, analyzed, collected, then explained to provide answers about the phenomenon that occurs. Then, explain the relationship, the hypothesis test, and the conclusions of the analysis obtained. The results showed that a value of 1,172 is a (constant) indicating that if there is no earth tax burden then the production rate will reach 1,172. Based on the results of data processing obtained the value of t area of land by = 1,274 with a probability of 0.000 <0.05, so that the area of land is significant to soybean farming income.